MENINGKATKAN HASIL BELAJAR SISWA DENGAN MODEL SNOWBALL THROWING PADA POKOK BAHASAN PENYELESAIAN PERTIDAKSAMAAN KUADRAT - Ama, Ferdinandus Tamo; Sartati, Setiawan Budi (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2018)
[Title: Improving Student Learning Outcomes with the Snowball Throwing Model in the Subject of Solving Inequality Squared] The problem raised in this study is the low student learning outcomes. The research objectives are to improve student learning outcomes. The researcher wants to solve this problem by applying the snowball throwing model on the subject of solving the inequality squared in class X IPA 1 Manda Elu Private High School. This type of research is classroom action research (CAR) with two planned cycles. For each cycle consists of five stages, namely planning, implementing actions, observing, evaluating, and reflecting. The research subjects were teachers (researchers) and students of class X IPA 1 at Manda Elu Private High School. Collecting data in this study using written tests and observation sheets. The research data were analyzed descriptively-quantitative for test result data and descriptive-qualitative data for observation. The results showed that student learning outcomes improved, this can be seen from the percentage of classical completeness that is the first cycle of 54.3% increased in the second cycle 80%. From the results of the first cycle and second cycle increased, which means that more and more students received grades ?65 (KKM). Based on the results of the study it can be concluded that the application of the snowball throwing model on the subject of solving the inequality squared can improve learning outcomes of class X students of Manda Elu Private High School.